PEMANFAATAN LIMBAH PRODUK PERTANIAN DALAM PAKAN BUATAN YANG BERPROBIOTIK TERHADAP EFISIENSI PAKAN, PERTUMBUHAN, DAN KELULUSHIDUPAN LELE DUMBO (Clarias gariepinus) DALAM PRODUKSI KULTUR MASAL - Suminto ,; Titik Susilowati; Sarjito ,; Diana Chilmawati (Fakultas Perikanan Universitas Pekalongan, 2019)
Dumbo catfish (Clarias gariepinus) Sangkuriang strain is the consumption of freshwater fish that is much favored by many people, because its high nutrition and low price. The high price of feed and the low efficiency of feed utilization are an obstacle in the development of African catfish cultivation. The purpose of this study was to determine the use of agricultural product wastes such as corn flour, wheat, soybean meal, curry and chicken eggs that have been made as pellet feed containing 32.58% protein, with the addition of probiotics (A) and without the addition of probiotics (B) on the efficiency of feed utilization, growth and survival of African catfish (C. gariepinus).This study used an experimental method by designed through a completely randomized design (CRD) with two treatments and each of three replications, respectively. The test fish seed used was African catfish (C. gariepinus) with an average weight of 2.04 ± 0.05 g and an initial density of 350 tails / m2 of pond area with a culture period during 60 days. The results of this study that self-made feed with material from agricultural wastes were sufficient to provide the results of the value of feed utilization efficiency (FUE) of 84.10 ± 1.83%, feed conversion ratio (FCR) of 1.03 ± 0.02, and survival rate (SR)of 95.79 ± 0.16%. The addition of probiotics to self-made feed with raw materials from agricultural wastes had a significant effect (p <0.05) to produce feed utilization efficiency (FUE)of 99.56 ± 5.64%, feed conversion ratio (FCR)of 0, 88 ± 0.04, relative growth rate (RGR) of 14.77 ± 0.66% / day, and the survival rate (SR) of 98.92 ± 0.29%, which has a higher value than feeding without probiotics.